(untitled) (Revista de História da UEG (REVHIST), 2025)
This article aims is to analyze the installations of Indústrias Reunidas Francisco Matarazzo (IRFM) in the Água Branca neighborhood (São Paulo - SP) to discuss the limits and advances about the patrimonial politics towards the industrial heritage. Based on the case study, it is hoped to trace a genealogy for the formation of this knowledge area and to indicate some of its uses towards building an industrial workers’ memory. To reach this, the concept of lieux de mémoire (sites of memory) developed by Pierre Nora is mobilized to argue about the secondary place of the workers’ memory in the history of the city São Paulo. Finally, popular initiatives are emphasized to build peripheral memories as a possibility for the expansion of the field, such as the Centro de Memória Queixadas Sebastião Silva de Souza, in the Perus neighborhood. Keywords: industrial heritage; post legal protection; memory; Indústrias Matarazzo.